VALIDITAS DAN EFEKTIFITAS HUKUM ADAT TENTANG PENGELOLAAN LINGKUNGAN HIDUP DI DESA ADAT PENGLIPURAN - I Gede Januariawan; I Nyoman Nadra (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Exploitation of natural resources without regard tosustainability causes environmental damage. Environmental damage will ultimately reduce the quality of human life. Natural disasters such as floods, landslides, global warming and climate change are the result of environmental damage. Penglipuran Traditional Village is located in the Kubu Village area, Bangli District. It is interesting to do research in this village because the community is able to maintain environmental sustainability well. It is interesting to do research in this village because the community is able to maintain environmental sustainability well. The author's initial observations show that people do not know about the laws and regulations governing the environment. The community maintains, preserves their environment, because they follow the customary rules that apply in the Penglipuran Traditional Village.This study examines the validity and effectiveness of the Validity and Effectiveness of Customary Law on Environmental Management in Penglipuran Traditional Village. The data were obtained by in-depth interview techniques, observation, and by conducting a literature study. The discussion using the theory of legal effectiveness from Hans Kelsen is used to discuss the first problem. The second problem in this study will be discussed with the theory of validity and law enforcement. The third problem in this study will be discussed with the theory of legal validity. This theory explains how and what the conditions are so that a legal method becomes legitimate and valid or valid, so that it can be applied to the community and can be forced.The analysis shows that the Penglipuran community can still survive to preserve their environment because the customary village community adheres to the provisions of the Customary Law contained in awig-awig and perarem. The rules of customary law regarding environmental conservation meet the requirements for the validity of a legal rule so that it is effective. The rules of customary law also meet the requirements for social, juridical and moral applicability.